Politik Wacana Over Claiming Wayang sebagai Identitas Intangible Heritage Indonesia dan Malaysia - Sandi Vindiyan Jaya Kusuma (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2021)
This study aims to analyze the discourse politics of over-claiming wayang as the intangible heritage identity of Indonesia and Malaysia in a daily news item on the internet. This research method uses Norman Fairclough's critical discourse analysis theory to determine what discourses are presented in the daily news on these internet news sources. The data obtained to be presented primary data derived from daily internet news and secondary data from several related articles that have discussed this case then viewed from a political perspective on identity and cultural disputes. This study indicates that the influence of cultural discourse on Wayang Kulit as native Indonesian culture also needs to be considered with the importance of a country's identity from a cultural aspect. In conclusion, political discourse is carried out as an affirmation of Indonesian identity to make Malaysia understand that wayang is one of the cultural identities of the Indonesian nation. Keywords: Identity, Indonesia, Malaysia, Discourse Politics, Wayang Kulit